The marginal voter's curse - Helios Herrera; Aniol Llorente-Saguer; Joseph C. McMurray (Queen Mary University of London, School of Economics and Finance, 2016)
This paper proposes a rational model of voter participation by generalizing a common-value model of costless voting to include not just pivotal voting but also marginal voting incentives. A new strategic incentive for abstention arises in that case, to avoid the marginal voter's curse of pushing the policy outcome in the wrong direction. The marginal voter's curse presents a larger disincentive for voting than the swing voter's curse. Moreover, marginal motivations are shown to dominate pivotal motivations in large elections. Model predictions are confirmed in a laboratory experiment and applied in a comparative analysis of electoral rules.
Keywords: C72; C92; D70; 330; Turnout; Information aggregation; Underdog effect; Experiment